IMPROVING RISK MANAGEMENT IN THE ACTIVITIES OF INSURANCE ORGANIZATIONS OF UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The article examines the role and significance of international standards in improving risk management in the activities of insurance organizations of the Republic of Uzbekistan. The relevance of the study is driven by the transformation of the national insurance market under the conditions of integration into global financial processes and the introduction of new risk-based regulatory standards. The purpose of the research is to assess the applicability and expected impact of international standards on the quality of the risk management system of insurers in Uzbekistan, as well as to formulate practical recommendations for the regulator and market participants.
Keywords: Risk Management, ERM, ORSA, IFRS 17, Solvency II, Insurance Market, International Standards.